A pragmatic randomized controlled trial to evaluate the effectiveness of a facilitated exercise intervention as a treatment for postnatal depression: the PAM-PeRS trial. Issue 11 (August 2015) - Daley, A. J.; Blamey, R. V.; Jolly, K.; Roalfe, A. K.; Turner, K. M.; Coleman, S.; McGuinness, M.; Jones, I.; Sharp, D. J.; MacArthur, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Postnatal depression affects about 10–15% of women in the year after giving birth. Many women and healthcare professionals would like an effective and accessible non-pharmacological treatment for postnatal depression. Method Women who fulfilled the International Classification of Diseases (ICD)-10 criteria for major depression in the first 6 months postnatally were randomized to receive usual care plus a facilitated exercise intervention or usual care only. The intervention involved two face-to-face consultations and two telephone support calls with a physical activity facilitator over 6 months to support participants to engage in regular exercise. The primary outcome was symptoms of depression using the Edinburgh Postnatal Depression Scale (EPDS) at 6 months post-randomization. Secondary outcomes included EPDS score as a binary variable (recovered and improved) at 6 and 12 months post-randomization. Results A total of 146 women were potentially eligible and 94 were randomized. Of these, 34% reported thoughts of self-harming at baseline. After adjusting for baseline EPDS, analyses revealed a −2.04 mean difference in EPDS score, favouring the exercise group [95% confidence interval (CI) −4.11 to 0.03, p = 0.05]. When also adjusting for pre-specified demographic variables the effect was larger and statistically significant (mean difference = −2.26, 95% CI −4.36 to −0.16, p = 0.03). Based on EPDS score a larger proportion of the intervention group was recovered (46.5% v. 23.8%, p = 0.03) compared with usual care at 6 months follow-up. Conclusions This trial shows that an exercise intervention that involved encouragement to exercise and to seek out social support to exercise may be an effective treatment for women with postnatal depression, including those with thoughts of self-harming.